2021
DOI: 10.1111/jfcj.12207
|View full text |Cite
|
Sign up to set email alerts
|

“Man Up”: Sex‐Differentiated Pathways of Juvenile Delinquency through Trauma, Borderline Traits & Offense Patterns

Abstract: Juvenile delinquency presents a significant fiscal and moral cost to society; given the ability for early intervention and changing offending trajectories, it is essential to understand potential risk factors and offending patterns in justice‐involved youth. The current study examined features of 193 male and 96 female profiles on the Personality Assessment Inventory – Adolescent (PAI‐A) in conjunction with offending patterns to determine sex differences in offending. Significant sex effects on status offendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Furthermore, these results suggest that intervention programing should also include appropriate wellness assessments in their intake process as youth involved in delinquency are likely to have issues with wellness that need to be addressed. Additionally, the significant inverse relationship of age with the likelihood of delinquency for five of the six groups suggests the need for early prevention and intervention, of course in line with prior research (Cohen et al, 2010;Mann & Reynolds, 2006;McGill & Stefurak, 2021).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore, these results suggest that intervention programing should also include appropriate wellness assessments in their intake process as youth involved in delinquency are likely to have issues with wellness that need to be addressed. Additionally, the significant inverse relationship of age with the likelihood of delinquency for five of the six groups suggests the need for early prevention and intervention, of course in line with prior research (Cohen et al, 2010;Mann & Reynolds, 2006;McGill & Stefurak, 2021).…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, different dimensions of wellness may predict different types of offending and this relationship could certainly be shaped by gender/race. Indeed, prior research has found that different types of trauma predict different types of delinquent offending (McGill & Stefurak, 2021) and physical health moderates the relationship between strain and different types of delinquent offending (Hancock, 2021).…”
Section: Limitationsmentioning
confidence: 99%